Clinical case of management of the patient with depressive disorder and systemic lupus erytematosus - Danchenko, Anastasiia (Psychosomatic Medicine and General Practice, 2020)
This case report describes authors own experience of clinical mamgmemt of the patient with depressive disorder and systemic lupus erytematosus (SLE).